2012
DOI: 10.1016/j.meatsci.2012.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Beef carcasses with larger eye muscle areas, lower ossification scores and improved nutrition have a lower incidence of dark cutting

Abstract: ÔØ Å ÒÙ× Ö ÔØBeef carcasses with larger eye muscle areas, lower ossification scores and improved nutrition have a lower incidence of dark cutting This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 20 publications
6
36
1
4
Order By: Relevance
“…one-half the incidence of dark cutting than those weighing less than 272 kg. Increased carcass weight may reduce the incidence of dark cutting because heavy carcasses are most likely to have increased muscle glycogen reserves (McGilchrist et al 2012), a slowed chilling rate, and a rapid decline in post-mortem pH (Cliplef et al 1989;Wulf et al 1997;Aalhus et al 2001). These results agree with previous research which found that heifer carcasses that cut dark were associated with decreased mean carcass weight (Cliplef et al 1989;Murray 1989).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…one-half the incidence of dark cutting than those weighing less than 272 kg. Increased carcass weight may reduce the incidence of dark cutting because heavy carcasses are most likely to have increased muscle glycogen reserves (McGilchrist et al 2012), a slowed chilling rate, and a rapid decline in post-mortem pH (Cliplef et al 1989;Wulf et al 1997;Aalhus et al 2001). These results agree with previous research which found that heifer carcasses that cut dark were associated with decreased mean carcass weight (Cliplef et al 1989;Murray 1989).…”
Section: Discussionsupporting
confidence: 88%
“…McGilchrist et al (2012) reflected that increased muscularity and fatness most likely indicated improved nutrition of the cattle and increased muscle glycogen reserves; however, increased musculature in the study of Hawrysh et al (1985) was linked to increased dark cutting and was most likely indicative of rapidly growing cattle with reduced muscle energy reserves. Additionally, muscular animals with an increased proportion of fast muscle fibers (Wegner et al 2000) may be most at risk of dark cutting with acute activity such as fighting or physical combat before slaughter, which greatly lowers muscle glycogen (Lacourt and Tarrant, 1985;McGilchrist et al 2011).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Vealers and grain-fed animals had~50% of the lighter 1B and 1C meat colour scores and older animals had the highest incidence of dark cutting (33%). Muscles from older animals are well known to exhibit darker coloured meat (Page et al 2001;Mlynek and Gulinski 2007;McGilchrist et al 2012). This reduction in lightness is most likely to be caused by an increase in myoglobin concentration and lower numbers of large 'white' fast glycolytic fibres and more 'red' slow oxidative fibres (Moon et al 2006;Mlynek and Gulinski 2007).…”
Section: Animal Factorsmentioning
confidence: 99%